2008
DOI: 10.1007/s10741-008-9126-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of thyroid hormone in the pathophysiology of heart failure: clinical evidence

Abstract: Thyroid hormone (TH) has a fundamental role in cardiovascular homeostasis in both physiological and pathological conditions, influencing cardiac contractility, heart rate (HR), diastolic function and systemic vascular resistance (SVR) through genomic and non-genomic mediated effects. In heart failure (HF) the main alteration of thyroid function is referred to as "low-triiodothyronine (T3) syndrome" (LT3S) characterized by decreased total serum T3 and free T3 (fT3) with normal levels of thyroxine (T4) and thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 155 publications
2
91
0
2
Order By: Relevance
“…Thyroid function abnormalities may predict poor prognosis as high BNP levels (39)(40)(41). Previously, we have shown that decreased fT3/fT4 ratio might predict worse outcome in patients with dilated cardiomyopathy (41).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid function abnormalities may predict poor prognosis as high BNP levels (39)(40)(41). Previously, we have shown that decreased fT3/fT4 ratio might predict worse outcome in patients with dilated cardiomyopathy (41).…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in treating HF in the last 15 years, the prognosis of this dysfunction remains poor (6). In recent years, untreated overt hyperthyroidism and hypothyroidism have been reported to be common causes of HF (7,8,9,10). Moreover, persistent subclinical thyroid dysfunction has recently been associated with the development of HF in patients with and without underlying heart disease (11,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…1 Therefore, the low T3 syndrome has been established as a strong predictor of death in the cardiac, non-surgical patients. 3,7 Since cardiac surgery may bring about important alterations of the thyroid function, the postoperative low T3 syndrome has been the object of intense research during the last twenty years. The results of this study demonstrate that the presence of the low T3 syndrome at hospital admission is associated with a markedly increased risk of postoperative myocardial dysfunction and death in patients undergoing CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
“…T3 administration has been shown to prevent myocardial fibrosis in aortic banded animals, and to regulate the collagen type I biosynthesis. 7 Finally, thyroid hormone deficiency is known to be associated with important alterations of the coronary blood flow due to a rarefaction in the myocardial arterioles, and with ischemic myocite loss. 7 In light of these experimental evidences, the hypothesis that the increased incidence of postoperative low cardiac output and death that we observed in patients with low T3 is at least in part due to molecular and structural alterations of the myocardium, related to the reduced fT3 availability, seems extremely likely.…”
Section: Discussionmentioning
confidence: 99%